Mechanical properties of eco-friendly one-part metakaolin-based geopolymer concrete with Recycled Glass and Plastic (RESIN8) aggregates - Ajayi, Babatunde Luke (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.